Towards the Coexistence of Global and Local Socioeconomic Urban Conditions: Comparing Glocalization in Bangkok, Thailand - Nattanich Meesang (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Urbanization and globalization have transformed Bangkok from a traditional, community-centered settlement into a vertical metropolis shaped by global capital and economic modernization. As Thailand’s economic hub, Bangkok thrives on trade, tourism, and investment, but this growth often costs cultural identity and socio-economic equity. While globalization fosters opportunities, it also brings income inequality, labor exploitation, and cultural homogenization. The dominance of international businesses in Sukhumvit displaces local communities, dilutes Thai heritage, and challenges SMEs facing regulatory hurdles. Conversely, Bantadthong exemplifies a "glocal place," balancing cultural heritage preservation with sustainable development. Its approach integrates modernization without compromising local identity. These challenges highlight the need for balanced policies integrating global practices while preserving cultural continuity. This study evaluates glocal development strategies through case studies, exploring urban policies that bridge global business models with local contexts. It aims to ensure Bangkok remains competitive and culturally distinct as a thriving global city.